Design of a Battery-Ultracapacitor Hybrid Energy Storage System with Power Flow Control for an Electric Vehicle - Boon Kai Tan; Nadia M. L. Tan; Agileswari Ramasamy (Institute of Advanced Engineering and Science, 2018)
A combination of battery and ultracapacitor as a hybrid energy storage system (HESS) of an electric vehicle (EV) can result in better acceleration performance, reduce battery charge-discharge cycle and longer driving range. This paper presents a new converter design combining triple-half-bridge (THB) and buck-boost half-bridge (BHB) converters in a battery-ultracapacitor HESS. The BHB converter is used to compensate the voltage variation of the ultracapacitor. A power management system is proposed to control the power of battery and ultracapacitor to supply the demanded power. This paper describes the operation of the proposed converter using a simplified ∆-type primary-referred equivalent circuit. This paper also shows the simulation results verifying the dynamic response of the proposed power management system for the proposed HESS.